Family farming schools - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Seeing a son or daughter heading off to town to hunt for work has been a sadly familiar sight for farmers across the ages. It conjures up three fears: the end of the family farm, depopulation of the village and ? too often ? the return of the...